Strategi Berbasis Aktivitas Fisik dalam Mengatasi Stres dan Kecemasan: Tinjauan Empiris dan Rekomendasi Kebijakan - Pitaloka Priasmoro, Dian; Asri, Yuni; Della, Nanda; Nur Amalina, Ayu; Mulyana (Jurnal Keperawatan Muhammadiyah, 2025)
Background: Stress and anxiety have become significant mental health challenges in the modern era. In addition to pharmacological and psychological therapies, physical activity is increasingly recognized as an effective strategy for managing mental health. Objective: This study aims to evaluate the effectiveness of physical activity in reducing stress and anxiety and provide evidence-based policy recommendations. Methods: This study employs a systematic literature review, sourcing data from EBSCO, ScienceDirect, ResearchGate, IEEE Access, and DOAJ. The analysis follows the PRISMA framework, consisting of six key stages: defining the research question, identifying relevant studies, selecting studies, mapping data, synthesizing results, and expert consultation. Results: Regular moderate-intensity physical activity, such as jogging, yoga, and cycling, has been found effective in reducing stress and anxiety through the release of endorphins and serotonin. Additionally, participation in group exercise activities enhances social support, further benefiting mental health. Conclusion: Physical activity is an effective non-pharmacological intervention and should be integrated into public health policies. Greater access to community-based exercise programs is needed to support mental health initiatives.